Giant Schwannoma of Median Nerve at Forearm - Chowdhury, FH; Haque, MR; Islam, MS; Sarkar, MH (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Schwannomas are common benign nerve tumors occurring in the peripheral nerves. A very large schwannoma of more than 7 years duration, originating from the median nerve in the forearm in a 40 years old woman, is reported. There was numbness and tingling sensation in the forearm and hand. It was 18 cm in length and 8 cm in diameter. On the palm, there were signs of sensory disturbance with atrophy on the thenar muscles. Surgical removal was performed under operating microscope by separating the nerve fascicles from the tumor. There were 2 more tumors (1.5x2cm) on median nerve at elbow above the mentioned one. Histological examination revealed schwannoma. At 3.5 year follow-up, the patient was asymptomatic with excellent relief of symptoms with good forearm and hand motor function, though thenar atrophy persisted. The tumor did not recur. Although cases have been reported in the literature, this is probably the largest ever described with 2 more adjacent schwannomas. Key words: Median nerve, Giant schwannoma, Forearm DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9441 JBCPS 2011; 29(3): 174-176